Orally dissolving yoghurt strip: a new approach in delivery of probiotics - Saleena, Lejaniya Abdul Kalam; Nyam, Kar Lin; Yusof, Yus Aniza; Song, Adelene Ai-Lian; In, Lionel Lian Aun; Pui, Liew Phing (Springer, 2024)
The study focused on developing functional yoghurt edible film oral strip encapsulating viable probiotics (Streptococcus thermophilus (S. thermophilus), Lactobacillus bulgaricus (L. bulgaricus), and Lactococcus lactis (L. lactis)) with pectin biopolymer. The oral strip was optimized with Central Composite Design using independent variables such as functional yoghurt powder (2.5% w/v–7.5% w/v), pectin (1.5% w/v–2.5% w/v), and glycerol (55% w/w–65% w/w). The optimum oral strip was prepared at 7.5% (w/v) yoghurt powder, 2.5% (w/v) pectin, and 57.18% (w/w) glycerol, respectively. The oral strip developed with S. thermophilus, L. bulgaricus, and L. lactis had viability of 8.57 ± 0.04, 8.35 ± 0.04 and 8.44 ± 0.04 (log CFU/strip). Antibacterial zone of inhibition against Klebsiella pneumoniae and Pseudomonas aeruginosa were 12.00 ± 1.00 mm and 11.67 ± 0.58 mm accordingly. Optimized oral strip had moisture content of 9.85 ± 0.25 (%), colour difference (∆E) of 48.19 ± 1.30, tensile strength of 2.82 ± 0.07 (MPa), elongation at break of 12.68 ± 0.45 (%) and Youngs modulus as of 0.22 ± 0.01, respectively. Additionally, scanning electron microscopy of oral strip showed well-incorporated yoghurt powder in the film matrix. In the present study, nutritional improvements were developed with acceptable functional properties and probiotic viability.